HUBUNGAN LAMA SIMPAN DENGAN KARAKTERISTIK MUTU PADA BEBERAPA FORMULASI KRIM EKSTRAK KUNYIT (Curcuma domestica Val.) - Natalie, Anita; Mulyani, Sri; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 4 (2017): Desember, 2017)
The purpose of this research were to know the relation of shelf  life with the characteristics cream of turmeric extract ( Curcuma domestica Val.) from some formulations and to determine the formulation which has the quality characteristics of cream of turmeric extract ( Curcuma domestica Val.) that have fullfilled the standard. This research consist  4 formulations which each formulation was repeated 2 times and observed every week for 5 weeks. The observed data were analyzed by using regression and correlation analysis. Observation parameters: homogenity, separation ratio, dispersive power, adhesion, pH, viscosity, total microbial. The regression for 5 weeks of all formulations on the viscosity characteristics ranged from 0.4167 - 0.9527, dispersive power ranged from 0.8679 - 0.9913,  adhesiveness ranged from 0.8386 - 0.9662 and the pH ranged from 0 , 3421 - 0.9774. All formulations have fullfilled the SNI standards of cream homogenity, separation ratio, viscosity, Permenkes standards are the characteristics of active substances and preservatives and have fullfilled the Perkabpomri standard is the total characteristics of microbial, with the best formulation is the formulation 1. Characteristics of cream extract of turmeric produced is homogeneous, no separation, no microbial, dispersive power 5.2 - 6 cm, viscosity 28,000 - 43,000 cP, adhesiveness 5,48 - 15,12 s, pH 7,64 - 8,1. Keywords: cream of turmeric extract, characteristic of cream, formulation, regression